(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article discusses the theoretical and practical aspects of reviewing court decisions by way of audit in the Economic Justice of the Republic of Uzbekistan. The goals and objectives of the audit authority in the world are explored, mainly on the basis of similar models of the countries of the Commonwealth of Independent States, summarizing the scientific and theoretical views of various scientists. It is concluded that in order to ensure a clear and uniform consideration of cases in the auditing authority, it is advisable to adopt a resolution of the Plenum of the Supreme Court of the Republic of Uzbekistan, containing clarifications on the application of legal norms.